Exploring barriers faced by women leaders in accessing and holding leadership positions in public universities in an emerging country - Islam, Md Asadul; Jantan, Amer Hamzah; Hunt, Abigail; Hashim, Haslinda; Chong, Choo Wei (Inderscience Publishers, 2022)
This study explored barriers faced by women in accessing and holding leadership positions in public universities in Malaysia. Semi-structured interviews with 12 deans from six public universities located in Selangor, Malaysia, were conducted for empirical data collection. This study finds internal politics, male domination, lack of benefits (both financial and non-financial), and biases of top management personnel as the organisational barriers faced by women in accessing leadership positions. However, whilst subsequent organisational barriers are similar to the organisational barriers identified in accessing positions, the negative perception of colleagues and their lack of support, together with lack of childcare facilities, have also emerged as barriers for women who already hold leadership positions in the public universities of Malaysia. Finally, implications of the findings, limitations and suggestions for future research are discussed.